The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/bkcs.11431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2O on Slurry‐Phase Fischer–Tropsch Synthesis over Alumina‐supported Cobalt Catalysts

Abstract: In this article, the hydrothermal stability and change in the physicochemical properties of supported cobalt catalysts modified with Zn, P, and Zr have been studied for slurry‐phase Fischer–Tropsch synthesis (FTS) at 230°C and 2.0 MPa. The Co/P/γ‐Al2O3 exhibited weaker interactions between cobalt oxides and alumina support than other catalysts. The support of all the Co catalysts underwent phase transformation of γ‐Al2O3 into boehmite (AlO(OH)) during hydrothermal treatment at 250°C for 12 h, except Co/P/γ‐Al2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In this sense, Liotta et al [19] reported that adding Ba during the sol-gel synthesis of Al 2 O 3 decreased diffusion of the Co 2+ ions into the structure of the alumina after Co deposition. Similarly, Park et al [20] and Park et al [21], on different studies, observed that adding phosphorus to Al 2 O 3 resulted in the formation of a mixed AlPO 4 phase that partially suppressed the formation of CoAl 2 O 4 . On the other hand, Cheng et al [22] found out that the addition of Mn or Fe during the synthesis of a Cu-Co/Al 2 O 3 catalyst improved the redox properties of both active metals.…”
Section: Introductionmentioning
confidence: 82%
“…In this sense, Liotta et al [19] reported that adding Ba during the sol-gel synthesis of Al 2 O 3 decreased diffusion of the Co 2+ ions into the structure of the alumina after Co deposition. Similarly, Park et al [20] and Park et al [21], on different studies, observed that adding phosphorus to Al 2 O 3 resulted in the formation of a mixed AlPO 4 phase that partially suppressed the formation of CoAl 2 O 4 . On the other hand, Cheng et al [22] found out that the addition of Mn or Fe during the synthesis of a Cu-Co/Al 2 O 3 catalyst improved the redox properties of both active metals.…”
Section: Introductionmentioning
confidence: 82%